The company in the Social Doctrine of the Church from John Paul II to Francis: a review (Cultura Económica, 2022)
This article examines the ideas about business developed by Popes John Paul II, Benedict XVI and Francis from Laborem Exercens to Fratelli tutti, the Compendium of the Social Doctrine of the Church and the document “The vocation of the business leader” of the Pontifical Council for Justice and Peace. Likewise, it collects the analyzes of existing authors. Finally, through this tour, we try to show the possible new avenues of research on social doctrine in business matters that have not yet been fully explored, as well as to propose some practical applications to researchers and businessmen.
Keywords: SOCIAL DOCTRINE OF CATHOLIC CHURCH; LABOREM EXERCENS; CENTESIMUS ANNUS; CARITAS IN VERITATE; LAUDATO SI’; FRATELLI TUTTI; COMPANY; BUSINESSMEN; BUSINESS LEADER; INTEGRAL DEVELOPMENT OF MAN